Analisis peran orang tua dalam pendampingan belajar peserta didik sekolah dasar - Rahmawan, Pratadina Arya; Rukayah, Rukayah; Ardiansyah, Roy (Universitas Sebelas Maret, 2022)
This study aims to describe the results of the Analysis of the Role of Parents in Student Learning Assistance. This study discusses the role of parents in student learning assistance which takes place at the subject's home, namely in Karang Tengah Hamlet, Jatipuro Village, Karanganyar Regency, Central Java. This study uses a type of qualitative research. This research uses a case study approach with qualitative methods. Techniques in collecting data are observation, interviews, and documentation. The subject of this study was one student at SD Negeri 02 Jatipuro. The data analysis technique used is technical triangulation. The results of the research show that the role of parents in assisting students' learning varies and plays a role in supporting children's learning processes. Parents have given the best role to help students in learning by providing assistance, motivation, role models, and facilities. The results of this study indicate that parents play a very important role in the child's learning process. Based on this research, it can be concluded that the role of parents (Mr. Mardi and Mrs. Sri Wahyuni) in assisting students in learning has shown the role of parents, namely first, carrying out the process of accompanying learning by providing several examples in solving problems and providing suggestions for trying various solution method. Second, giving encouragement to children in learning to help children produce their own ideas in the form of giving awards in the form of goods or praise. Third, set a good example by inviting children and asking them to try to implement the ideas that children convey by adjusting the child's abilities and linking them to everyday life. Fourth, provide good facilities in the form of a good room or environment.